PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten In - Utama, Reno Julia; Tanjung, Amries Rusli; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Competence of Human Resources, Information Technology Utilization, Implementation of Regional Financial Accounting System and Internal Control System on the Quality of Regional Financial Statements. This study was a quantitative research. Sample determined by purposive sampling and sampling for each SKPD using nonpropabilitas. The sample in this research as much as 75, who served as the fourth echelon in the regional work units (SKPD) in Indragiri Hulu. The sampling technique used purposive sampling method. Data of this study uses primary data directly through a questionnaire and analyzed using SPSS 20Management and analysis of data using multiple linear analysis with the help of software V20 (Statistical Produck and Service Solution). The results showed that the competence of Human Resources, Information Technology Utilization, Implementation of Regional Financial Accounting System and Internal Control System positive influence on quality of Regional Financial Statements. The coefficient of determination in this study was 97.4%, while 2.6% are influenced by other variables.Keyword : Competence, Technology, Financial, Internal Control, Financial Statement.